Identifikasi Perubahan Morfologi Kubah Lava Gunung Merapi Menggunakan DEM dari Foto Udara Tahun 2024-2025 - Jefry Ryan Yanuar Choiri; Rochmad Muryamto; Andika Bayu Aji (Journal of Geospatial Science and Technology, 2026)
Mount Merapi, located on the border of Central Java Province and the Special Region of Yogyakarta, is one of the most active volcanoes in Indonesia, characterized by repeated growth and reduction of lava domes. Morphological changes in the lava domes, particularly the central and southwest domes, play a crucial role in the generation of lava collapses and pyroclastic density currents that pose serious threats to surrounding settlements. Therefore, continuous monitoring of lava dome morphology, volume changes, and extrusion rates is essential for volcanic hazard assessment and mitigation. This study aims to map the morphological changes of Mount Merapi’s lava domes in both 2D and 3D, calculate volume variations, and analyze lava extrusion rates during the period from March 2024 to April 2025. The study utilized aerial photographs acquired by Unmanned Aerial Vehicles (UAVs) operated by the Center for Geological Disaster Technology Research and Development (BPPTKG). The aerial images were processed using Agisoft Metashape to generate orthophotos, Digital Elevation Models (DEMs), and tiled 3D models. Geometric accuracy was assessed based on the Regulation of the Head of the Geospatial Information Agency No. 18 of 2021. Volume changes were calculated using the cut and fill method, while extrusion rates were derived from volume differences between observation periods. The resulting 3D models were visualized through web-based scenes using ArcGIS Online, allowing interactive online access. The results indicate that the central lava dome experienced unstable changes, with two periods of volume reduction followed by a renewed growth phase. In contrast, the southwest lava dome exhibited significantly larger volume changes and higher extrusion rates, particularly between July 2024 and April 2025. These findings suggest that the southwest lava dome was the most active dome during the observation period and played a dominant role in controlling the morphological dynamics of Mount Merapi.